Boldine as a neuroprotective agent against motor neuron degeneration in models of amyotrophic lateral sclerosis - Toro, Carlos A.; Zhao, Wei; Garcia Silva, Patricio; Retamal-Santibáñez, Daniela; Rojas, Fabiola; Pan, Jiangping; Johnson, Nicholas; Duarte, Yorley; Cardozo, Christopher P.; Sáez, Juan C.; van Zundert, Brigitte (Frontiers in Cellular Neuroscience, 2025)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by motor neuron loss. Current FDA-approved treatments offer only modest benefits. Connexins (Cx), proteins that mediate intercellular communication have emerged as potential therapeutic targets, with increased Cx hemichannel (HC) activity observed in ALS models, and blocking Cx HC activity prevents motor neuron loss in vitro. Boldine, a natural compound with both Cx HC-blocking and antioxidant properties, has shown neuroprotective potential. This study investigated boldine’s effects in ALS models. In vitro, spinal cord cell cultures exposed to conditioned media from mutant SOD1G93A astrocytes showed a 50% reduction in motor neuron survival, elevated Cx HC activity, and increased reactive oxygen species (ROS). Boldine treatment significantly reduced Cx HC activity and ROS, and increased motor neuron viability. In vivo, oral boldine was well-tolerated in male mutant SOD1G93A mice starting at 7 weeks of age. Mice receiving 50 mg/kg/day showed a median survival increase of 9 days (132 vs. 123 days), though not statistically significant. Functional assessments revealed delayed disease progression: in the horizontal ladder rung walk test, boldine-treated mice exhibited a 36.8% reduction in crossing time and 21.2% fewer stepping errors. Improved scores were also observed on the Basso Mouse Scale at later stages, indicating preserved locomotor function. However, boldine had no significant effect in the rotarod test. These results support boldine’s neuroprotective effects in ALS, particularly in fine motor coordination and locomotor performance. Its reduction of Cx HC activity and oxidative stress highlights boldine’s promise as a potential therapeutic candidate for ALS.